Point-of-care optical biosensor platforms for stroke diagnostics with blood-based biomarkers - Harpaz, Dorin (Nanyang Technological University, 2020)
Stroke, a top leading cause of death, occurs as a result of an acute interruption in the brain blood flow. After stroke onset, brain cells die rapidly. Therefore, therapeutic treatment must be administered early. The ‘time is brain’ rational is a major limitation in therapeutic approaches, due to the association of time delays with worsen outcome in patients. Stroke diagnosis is mainly based on utilizing imaging technologies (magnetic resonance imaging (MRI) or computed tomography (CT)) in order to identify the stroke event in the brain. Stroke is classified to ischemic stroke (blockage) in 87% of cases, or to haemorrhagic stroke (bleeding) in the remaining 13% of cases. Then, ischemic stroke is further classified into different etiologies, based on the stroke mechanism: large artery atherosclerosis (LAA); cardioembolic (CEI); lacunar (LAC); others and undetermined. Stroke etiology classification main value is for therapeutic decision-making process, to allow the admission of time-limited window life-saving therapeutics (IV-tPA), within 4.5 hours from stroke onset. However, ischemic stroke etiologies classification schemes are complexed, time consuming (between hours to days), and require professional personal.